Functional interaction between nuclear inhibitor of protein phosphatase type 1 (NIPP1) and protein phosphatase type 1 (PP1) in Drosophila: consequences of over-expression of NIPP1 in flies and suppression by co-expression of PP1. - Parker, Louise (2002)
The catalytic subunit of type 1 Ser/Thr protein phosphatases (PP1c) forms complexes with many proteins that target it to particular subcellular locations and regulate its activity towards specific substrates. We report the identification of a Drosophila orthologue of nuclear inhibitor of PP1 (NIPP1Dm) through interaction with PP1c in the yeast two-hybrid system. NIPP1Dm shares many properties with mammalian NIPP1 including inhibition of PP1c in vitro, binding to RNA and PP1c, and localization to nuclear speckles. However, the mechanism controlling interaction of PP1c with NIPP1 is not conserved in Drosophila. NIPP1 can function independently of PP1c as a splicing factor, but the relative importance of this function is unknown. Over-expression of NIPP1Dm in Drosophila is cell-lethal in a range of tissues and developmental stages. The effects of ectopic NIPP1Dm are suppressed by co-expression of PP1c, indicating that the only effect of ectopic NIPP1Dm is to affect PP1c function. Co-expression of NIPP1Dm and PP1c does not have any detectable physiological effect in vivo, suggesting that the NIPP1Dm-PP1c holoenzyme is not normally limiting in Drosophila. These data show that NIPP1Dm and PP1c interact in vivo and suggest that NIPP1's role as a phosphatase regulator is conserved in Drosophila.